PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN SERTA IMPLIKASI PADA LOYALITAS NASABAH PT. RABOBANK INTERNASIONAL INDONESIA (Studi Kasus Pada Produk CASA dan DEPOSITO di Cabang Tanah Abang Jakarta) - Ahmad Rusmantowi (Universitas Mercu Buana, 2014)
Abstract. The aim of this research is to find out of the effect of quality products andpromotion towards customer satisfication and implication to customer loyality. Therespondents on this research are customers of CASA and time deposit on RabobankTanah Abang Branch, and they have become customer for at least 12 months. Thenumber of respondents is set of 100 respondents by using sampling technique. Thisresearch used analysis of Structural Equation Modeling (SEM). The results showed that:There is a positive correlation towards quality products with customer‘s satisfaction,promotion to customer‘s satisfaction, quality product and promotion of customer‘ssatisfaction, product with the customer‘s loyalty, promotion to customer‘s loyalty, andcustomer‘s satisfaction. Quality product, promotion towards the satisfication and loyalitycustumer, and there is no positive and significant correlation of quality product,promotion towards the loyality customer‘s through the customer‘s satisfaction as theintervening variable. Recommended for further researchers to expand the scope of theresearch is not just only one Rabobank Indonesia Branch but include of the othersRabobank Indonesia Branchs. Management of Rabobank Indonesia should to conductevaluation and improved the service in case of responsiveness by giving special trainingfor customer service to minimize complaintin order to increase satisfication and customerloyality.Keywords: Quality Product, Promotion, Satisfaction, and Customer Loyalty